The Mini-Craniotomy for cSDH Revisited: New Perspectives - Chen, Jefferson W.; Xu, Jordan C.; Malkasian, Dennis; Perez-Rosendahl, Mari A.; Tran, Diem Kieu (Frontiers in Neurology, 2021)
Background Chronic subdural hematomas (cSDH) are increasingly prevalent worldwide with the increased aging population and anticoagulant use. Different surgical, medical, and endovascular treatments have had varying success rates. Primary neurosurgical interventions include burr hole drainage of the cSDH and mini-craniotomies/craniotomies with or without fenestration of the inner membrane. A key assessment of the success or failure of cSDH treatments has been symptomatic recurrence rates which have historically ranged from 5 to 30%. Pre-operative prediction of the inner subdural membrane by CT scan was used to guide our decision to perform mini-craniotomies. Release of the inner membrane facilitates the expansion of the brain and likely improves glymphatic flow. Methods Consecutive mini-craniotomies(N=34) for cSDH evacuation performed by a single neurosurgeon at a quaternary academic medical center/Level I trauma center from July 2018-September 2020 were retrospectively reviewed. Patient characteristics (age, gender, presenting GCS, GOS, initial CTs noting the inner subdural membrane, midline shift(MLS), cSDH width, inner membrane fenestration, cSDH recurrence, post-operative seizures, infections, length of stay) were extracted from the EMR. Results 29 patients had mini-craniotomies as primary treatment of the cSDH. Mean age=68.9+19.7 years(range 22-102), mean pre-operative GCS=14.5+1.1, mean MLS=6.75+4.2 mm, and mean maximum thickness of cSDH=17.7+6.0 mm. 24 were unilateral, 5 bilateral, 34 total craniotomies were performed. 33 had inner membrane signs on pre-operative head CTs and an inner subdural membrane was fenestrated in all cases except for the one craniotomy that didn’t show these characteristic CT findings. Mean operating time=79.5+26.0 min. Radiographic and clinical improvement occurred in all patients. Mean improvement in MLS=3.852.69. There were no symptomatic recurrences, re-operations, surgical site infections, or deaths during the 6 months of follow-up. One patient was treated for post-operative seizures with AEDs for 6 months. Conclusion Pre-operative CT scans demonstrating inner subdural membranes may guide one to target the treatment to allow release of this tension band. Mini-craniotomy with careful fenestration of the inner membrane is very effective for this. Brain re-expansion and re-establishment of normal brain interstitial flow may be important in long term outcomes with cSDH and may be related to the recent interests in brain glymphatics and dural lymphatics.